Designing UI/UX on Adaptive Skills Learning Application for Autistic Children Using Design Thinking Method and Applied Behavior Analysis Theory - Putri, Yusnita; Saidah, Sofia (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2024)
This paper introduces he design of SemaiSelaras, an adaptive learning application tailored for children with Autism Spectrum Disorder (ASD), utilizing the Applied Behavior Analysis (ABA) theory and developed through the Design Thinking (DT) methodology. The application aims to address challenges faced by children with ASD in acquiring essential adaptive living skills. While prior studies have explored applications employing the DT methodology, this research uniquely focuses on integrating ABA theory to better meet the specific needs of users. The user-centered and iterative nature of DT ensured the application was designed to effectively address these requirements. The ABA approach, which breaks learning materials into manageable steps, supports children with ASD in gradually mastering life skills. SemaiSelaras integrates advanced technologies such as Optical Character Recognition (OCR), digital storyboard, audio discrimination learning, and video-based learning. The research contribution emphasizes the role of ICT in supporting accessibility and inclusion, helping children with ASD develop essential life skills. Usability testing was conducted using the System Usability Scale (SUS) and the SemaiSelaras prototype achieved an average score of 86.5, reflecting an excellent rating and demonstrating a high level of acceptance and usability for the application.